Forming Performance Assessment System of Risk Management in Railway Transport Companies - Chobitok, Viktoriya; Chumak, Larysa; Demianenko, Tetiana; Us, Yulia (International Journal of Engineering and Technology, 2018)
The paper discusses the problems of assessing risk management performance in railway transport companies. The authors developed an algorithm of forming the competitiveness and risk level assessment system for railway transport companies; they assessed the risk of competitiveness of Ukrainian railway industrial enterprises, suggested measures to mitigate the adverse effect of the risks, a mechanism of working out and making effective management decisions to neutralize risks for railway transport companies.Â